The professionalisation of Islamic religious education teachers - Tuna, Mehmet Hilmi (British Journal of religious education, 2022)
Although Islamic religious education (IRE) has been offered in Austrian public schools since 1982, public opinion and the general opinions of several stakeholders in the school system tend to be negative. One of the main reasons is the shortage of professionals, which led to recruiting personnel from different disciplines, who often lack the proper qualification for IRE. Public discourses do not consider the possibility of professionalisation after lateral entry into the career as an IRE teacher. Based on empirical research considering the biographical experiences and professional development of IRE teachers, the present paper examines how IRE teachers themselves perceive and asses their professionalisation and professionalism. The study’s findings show that professionalisation and recognition as a professional depend on many factors, such as the degree of teachers’ training and education at academic institutions, their work schedule, state accreditation, different types of employment contract, and more. The research results reveal, moreover, the different beliefs and views of IRE teachers regarding their profession and subject. This article focuses on the concept of performative competence staging as part of the professionalisation processes of IRE teachers in the Austrian context and beyond.